Design of a high-magnification and low-aberration compact catadioptric telescope for the Advanced Virgo gravitational-wave interferometric detector. (5th April 2017) - Buy, C; Genin, E; Barsuglia, M; Gouaty, R; Tacca, M
Abstract: Advanced Virgo is a major upgrade of the Virgo gravitational-wave detector, aiming to increase its sensitivity by an order of magnitude. Among the main modifications of the instrument, the size of the laser beam inside the central area has been roughly doubled. Consequently, the input/output optics systems have been re-designed. Due to the overall Advanced Virgo optical scheme, high-magnification and compact telescopes are needed. These telescopes also have to fulfill stringent requirements in terms of aberrations, separation of secondary beams and scattered light. In this paper we describe the design of the Advanced Virgo telescopes and their estimated performances in terms of tuning capability and optical properties.